(untitled) (Modern education and development, 2025)
This article aims to analyze fuzzy knowledge models and their applications, new approaches to the process of learning, understanding, and using knowledge and information. These knowledge models are widely used in various fields of society, especially in education, scientific research, artificial intelligence, technology, and social systems.